Land Development Strategy for Dilapidated Fabrics - Arman Khajeh Borj Sefidi (صفه)
Dilapidated fabrics are hubs of socioeconomic and environmentaldeficiencies formed as a result of exclusion from the socioeconomicprocesses of the city. Land development strategies employed forintervention in these fabrics are usually influenced by three factors:intervention objectives, profit margins and owners’ expectations.These strategies have and proven to be detrimental to the success ofall interventions. This research compares diverse land developmentstrategies with respect to these three intervention factors andsecond-tier factors influencing them. Prevailing processes, areaspecificconditions and community conditions influence intervention